APPLICATION OF INTERACTIVE LEARNING STRATEGIES TO IMPROVE STUDENT LEARNING OUTCOMES (A Pre-Experimental Study on the Civics Subject in Grade XI Science Class at MA Al-Barokah, Malangbong Subdistrict, Garut Regency) - Mulyani, Rini; Melati, Prima; Hermansyah; Darojat, Arik (Journal Civics And Social Studies, 2024)
This study aims to determine the application of interactive learning strategies in improving student learning outcomes in the subject of Citizenship Education (PKn) class XI MIPA MA Al-Barokah Malangbong. The place of this research is in Al-Barokah MA, Malangbong subdistrict, Garut regency. This type of research uses a quantitative method in the form of a pre-experimental design type of one group pretest-posttest design. The results showed an increase in student learning outcomes, as evidenced by the jump from the average pretest score of 58.77 in the category below the Minimum Completeness Criteria (KKM) to the posttest average score of 80.90 in the category beyond the Completeness Criteria Minimum (KKM). In addition, a gain value of 0.51 was obtained through the normalized gain test which placed this interpretation in the medium category with the percentage of student learning outcomes 36.7% indicating a high increase, 13.3% indicating no increase or being in a fixed category, 40% showed a moderate increase and 10% showed a low increase. Therefore, the application of interactive learning strategies can improve student learning outcomes.